2022
DOI: 10.35848/1347-4065/ac96b7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Co additive amount to improve thermoelectric properties of β-FeSi2

Abstract: The present manuscript deals with the synthesis of pure and Co-doped β-FeSi2 by conventional arc-melting method and the investigation of the effect of Co-dopant on the structural, electrical, and thermoelectric properties of β-Fe1-xCoxSi2 (0 ≤ x ≤ 0.06) from 300 to 800 K. The electrical resistivity decreases with increasing Co-doping due to the increase in carrier concentration. The Seebeck coefficient of all Co-doping samples (0.005 ≤ x ≤ 0.06) is higher and more stable than that of x = 0 due to the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…It is considered that both Fe1 and Fe2 are slightly changed with Ni addition. Therefore, the Ni population should equally occupy both Fe1 and Fe2 sites, which is similar to a previous study wherein Co was doped into the β-FeSi2 system [20,34]. Figure 4d shows the reliability factor Rwp with x dependences.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…It is considered that both Fe1 and Fe2 are slightly changed with Ni addition. Therefore, the Ni population should equally occupy both Fe1 and Fe2 sites, which is similar to a previous study wherein Co was doped into the β-FeSi2 system [20,34]. Figure 4d shows the reliability factor Rwp with x dependences.…”
Section: Resultssupporting
confidence: 82%
“…This result suggests that the proposed arc-melting and direct-heat-treatment method is efficient at fabricating a high-relative-density sample that contributes positively to the decrease in electrical resistivity, which is good for TE application. The three dimensions of the orthorhombic crystal structure of β-FeSi 2 were provided by our previous report [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the tendency of r of this Co-doped sample was uniform over the temperature range of 300-800 K. This is probably due to the low mobility (m H ) of around 3.5 cm 2 V À1 s À1 . 39 Interestingly, it has been reported that the tendency of r of Ni-doped b-Fe 1Àx Ni x Si 2 decreases with increasing temperature probably due to the higher m H in the range of 10-35 cm 2 V À1 s À1 . 40 Since we have previously found that the maximum ZT was obtained in the b-Fe 0.97 Co 0.03 Si 2 matrix prepared by arc-melting followed by a heat treatment process, 39 we attempt to improve the performance of b-Fe 0.97 Co 0.03 Si 2 prepared by the same fabrication process by alloying it with Ni in this work.…”
Section: Introductionmentioning
confidence: 98%